Pengaruh Wanita Dewan Direksi terhadap Firm Value melalui Firm Performance sebagai Variabel Intervening - Yurike Hamdani; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aims to examine the affect of woman in board on firm value and firm performance, and the affect of firm performance on firm value. This study also examine the indirect influence of woman in board on firm value through firm performance as intervening variable. Data were obtained from 60 firms listed in Indonesia Stock Exchange (IDX) in trade and consumer goods sector for the fiscal year of 2012-2015. Woman in board was measured by the proportion of woman in board of director. The value of the firm was measured by Tobin’s q. Firm performance was measured by ROA. The results showed that there is a positive affect of woman in board of directors on firm value, woman in board on firm performance, and firm performance on firm value. Furthermore, this study also found that firm performance is incapable in mediating the indirect influence of woman in board on firm value.